2018
DOI: 10.1111/plb.12937
|View full text |Cite
|
Sign up to set email alerts
|

Seed enhancing treatments: comparative analysis of germination characteristics of 23 key herbaceous species used in European restoration programmes

Abstract: The response of seeds from 23 wild plant species to a range of seed enhancing treatments was studied. We tested the hypothesis that sensitivity of the 23 species to these compounds is related to their ecological niche. The three ecological niches considered were open land, open-pioneer and woodland. Hence, the germination of a species is likely adapted to different light conditions and other environmental signals related to the niche.• As representatives of environmental signals, the effects of smoke-related c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 78 publications
2
2
0
Order By: Relevance
“…While the seeds of some did not germinate (or very few germinated) with no treatment, others had different responses (as regards GRP and GSP) to the various treatments. This is in agreement with [51] who, after analysing 23 key herbaceous species for use in European habitat restoration, found that differences exist among species in their responsiveness to various germination cues.…”
Section: Discussionsupporting
confidence: 92%
“…While the seeds of some did not germinate (or very few germinated) with no treatment, others had different responses (as regards GRP and GSP) to the various treatments. This is in agreement with [51] who, after analysing 23 key herbaceous species for use in European habitat restoration, found that differences exist among species in their responsiveness to various germination cues.…”
Section: Discussionsupporting
confidence: 92%
“…Our results confirm the information that cold–wet stratification (Russell, 2011) and GA 3 treatments (Del Egido et al, 2019; Kildisheva et al, 2019) are effective in dormant seeds without water penetration problems. Kırmızı et al (2018) and Yucel (2022) reported results parallel to our study.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, across a wide spectrum of 23 key herbaceous species for use in European habitat restoration, Lopez del Egido et al . () found that species that share a similar environment have similar light requirements for germination, while differences exist among species in their responsiveness to other germination cues. Consequently, enhancing germination may demand a species‐by‐species approach.…”
Section: Improving Seed Germinationmentioning
confidence: 99%